IR - spectroscopic characterization of biominerals in marattiaceaeus ferns - Baran, Enrique José (2010)
Frond samples of the eusporangiate ferns Marattiaceae genera Angiopteris, Christensenia, Danaea and Marattia were investigated by infrared spectroscopy, under different experimental conditions. The results confirmed the previously reported accumulation of biogenic silica (SiO2) in tissues of these ferns and also showed, for the first time, the presence of calcium oxalate in this group of plants, probably as weddellite. The ability to biomineralize SiO2, to produce and accumulate biogenic silica, is suggested now to be a general family trait of the Marattiaceae.